Electrostatic Separation of Minerals composed of Rare Earths: Capacsaya Project, Cusco - Ochoa, Joel (2018)
In this article we present the results of applying the technique of electrostatic separation to minerals containing rare earths. The presence of La, Ce, Sm, Pr and Nd in the initial sample was verified by ICP-MS analysis. Hematite and non-conductive minerals such as dolomite and feldspar-K were concentrated by electrostatic separation. On the other hand, through SEM-EDS it was proved that the rare earth elements belong to the monazite mineral (La, Ce, Nd) PO4 and that this is associated to Feldspar-K.